2020
DOI: 10.14744/jpd.2020.15_20
|View full text |Cite
|
Sign up to set email alerts
|

Assesment of the Impact of Severe Early Childhood Caries on the Quality of Life of Preschool Children and their Parents

Abstract: Objective: The aim of the present study was to assess the prevalence of the early childhood caries (S-ECC) and its impact on preschool children’s life (aged 4-6), as well as on their parents, in one of the most popular prefectures in Casablanca, Morocco. Materials and Methods: Parents of 546 children attending 11 randomly selected preschools (7 private and 4 public institutions) were invited to complete 13 items of an oral health questionnaire and had their children undergo a dental examination. The quality of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In Casablanca, Morocco, the prevalence of ECC and severe-ECC were 74.2 and 47.3%, respectively (17). Results of this study suggests also that ECC negatively impacts the life quality of Moroccan Children in addition to their parents.…”
Section: Discussionmentioning
confidence: 66%
“…In Casablanca, Morocco, the prevalence of ECC and severe-ECC were 74.2 and 47.3%, respectively (17). Results of this study suggests also that ECC negatively impacts the life quality of Moroccan Children in addition to their parents.…”
Section: Discussionmentioning
confidence: 66%
“…Furthermore, some of the patients referred from nearby private clinics for GA dental management were among those who could afford such treatment. Although many studies have found a higher prevalence of ECC in socially disadvantaged children, they may have not used or had limited access to dental care including DGA [2,11,14]. Only 30.4% of the total studied population used the public funded fee DGA for management of ECC in this study.…”
Section: Discussionmentioning
confidence: 79%
“…Early childhood caries (ECC) is defined by the American Academy of Pediatric Dentistry as "the presence of one or more decayed, missing, or filled teeth or surfaces in any primary tooth in a child under the age of 6 years [1]." Left untreated, it can lead to poor oral and general health, thus compromising the child's quality of life [2]. ECC remains a significant public health issue worldwide, with its prevalence in 3-yearold children ranging from 22% to 61% in the Middle East and 38% to 45% in Africa [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, the family's socioeconomic status was not associated with the child's oral health or with the child's quality of life. Similarly, Li et al reported no signi cant associations between gender or SES with ECOHIS [43]. However, few other studies have reported a high prevalence of ECC and mean scores for ECOHIS for children from families with lower socioeconomic status and with lower maternal education [38].…”
Section: Discussionmentioning
confidence: 99%